Evaluation of the potential of protective cultures to extend the microbial shelf-life of chilled lamb meat. (November 2021) - Xu, Michelle M.; Kaur, Mandeep; Pillidge, Christopher J.; Torley, Peter J.
Abstract: The use of protective cultures to inhibit spoilage bacteria is a promising natural preservation technique to extend the shelf-life of fresh meat. This study evaluated the effectiveness of six food-grade protective cultures (containing different combinations of Lactobacillus sakei, Pediococcus pentosaceus, Staphylococcus xylosus, and Staphylococcus carnosus ) on naturally contaminated chill-stored (4 °C) lamb meat in different packaging systems. Only slight reductions of common meat spoilage bacteria Brochothrix thermosphacta, Pseudomonas spp., and Enterobacteriaceae were observed in culture-treated samples stored in modified atmosphere packaging (80% O2 :20% CO2 ). Greater inhibitory effects were found in vacuum-packed lamb, with mixed cultures containing either L . sakei, S. carnosus, and S. xylosus or S. carnosus and L . sakei causing the most significant reductions. Protective cultures did not adversely affect meat color or pH. This study demonstrated the potential of protective cultures comprising lactic acid bacteria and coagulase-negative staphylococci in controlling microbial spoilage of lamb and, by inference, other types of meat as a natural solution for shelf-life extension. Graphical abstract: Unlabelled Image Highlights: Lactobacillus and Staphylococcus cultures suppressed lamb meat spoilage bacteria Antimicrobial activity varied depending on the culture species composition Cultures were more effective in meat packaged in vacuum than in modified atmosphere Meat color and pH were not negatively affected by the protective cultures